Tempoyak as a Typical Fermented Food from Jambi: A Study of the Integration of Tradition with Modern Food Technology Innovation - Yusfi, Liza Aulia; Ramadani, Suci Putri; Kharisma, Yulia; Sulistiana, Ika Putri; Pratami, Tesy (PUI BiGME Universitas Jambi, 2025)
Tempoyak, a traditional fermented food derived from durian (Durio zibethinus), which holds considerable cultural, nutritional, and health significance, and plays an important role in Jambi’s distinctive culinary heritage. This product is generally produced through spontaneous fermentation dominated by Lactic Acid Bacteria (LAB), which plays a crucial role in shaping its sensory attributes, texture, and antimicrobial properties. Nevertheless, such traditional fermentation practices often lead to inconsistent product quality due to variability in raw materials, fermentation conditions, and microbial composition. This review provides a comprehensive examination of the integration of modern food technologies aimed at improving the quality, safety, and functional potential of tempoyak, including molecular-based microbial identification, the use of starter cultures and standardized durian raw materials, as well as the application of innovative packaging technologies such as High Pressure Processing (HPP) and vacuum packaging. These approaches are anticipated to ensure more consistent and safe production of tempoyak, while simultaneously enhancing its functional and economic value, thereby reinforcing its recognition as a heritage food with global market potential.